Using Water Balance to Analyse Water Availability for Irrigation with Upraising Surface Temperature ( Acase Study Pasar Baru Barrage in Cisadane Watershed) - Ariyani, Dwi; Putuhena, Frederick Josep; Wira, Dharma (Civil and Environmental Science Journal (CIVENSE), 2020)
This research aims to determine the water balance between water demand and availability at Pasar Baru Barrage. Pasar Baru Barage supply irrigation water for 22.441 ha. Irrigation water requirements related to temperature, evapotranspiration, and precipitation. HigherÂ  air temperature in a region, influents the water requirement. This research was also conducted to see the effect of the rise in temperature of the water needs. The water requirement is calculated based on the needs of irrigation and domestic water to the raw water. For irrigation water needs calculated by planning a cropping pattern in one year in this study, it was planned to plant rice twice and once crop, evapotranspiration was calculated using the Penmann Modification method, so that water requirement in the intake area was obtained multiplying the area of irrigation. Calculation of water availability by using FJ Mock method, the maximum water availability value is 11.75 m3 / second. so that the water balance is obtained by the surplus deficit water balance method. After conducting this study, it can be seen that the air temperature in the cisadane weir of the new market is increasing from 1985 to 2018. The average temperature increases by 0.740C, the minimum air temperature increases by 0.80C and the maximum increases by 0.20C, the average evapotranspiration value decreases by 0.15 mm / day, while the average water availability decreases from the year 1985 to 2018 at 1.8 m3 / second, the amount of water needed for irrigation was 5.57 liters/ second/ha. Â The calculation of the water balance in the river is based on a reliable discharge, the result is a deficit every year from 1985 to 2018. So there is a need for Pasar Baru weir to overcome the lack of irrigation water every year, based on discharge data available at Pasar Baru weir from 2013 to 2015, it can seen that the water balance has a surplus every year, the water balance deficit only occurred in July 2015 of 0.3 m3 / sec. The largest water balance occurred in March 2014 amounting to 656.97 m3 / sec. The results of this study can be used as a reference in planning and developing integrated water resources buildings especially in the Cisadane watershed and the Ciliwung-Cisadane river basin in general.